(In)iustissima cognitio centurionum. I privilegi giuridici dei soldati secondo il poeta satirico - Costa, Stefano (Cultura giuridica e diritto vivente, 2020)
[(In)iustissima cognitio centurionum. The satyrical poet about soldiers' juridcal benefits] Juvenal’s 16th satire, dated for a long time to Severian age, is a lively polemic against military juridical privileges and abuses but records as well some otherwise unknown evidence in terms of lawsuit and organization of military trials.